Effects of Proficiency and Motivation on the Choices of Language Learning Strategies - Khamkhien, Attapol (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2012)
The objectives of this investigation were twofold: 1) to identify language learning strategies commonly used by Thai EFL learners, and 2) to determine the roles of three variables contributing to their strategy use: language proficiency and motivation. A set of questionnaires consisting of the Strategy Inventory for Language Learning (SILL), and the Motivated Strategies for Learning Questionnaire (MSLQ) was given to 1,405 Thai university students studying English. The analysis revealed that, in general, memory strategies were found to be the most common learning strategies, whereas social strategies were the least common. Motivation was reported to be the most significant variables affecting their choices of language learning strategies. The analysis revealed certain elucidating facts that can be utilized in future planning of English language teaching to improve the English performance of Thai learners.